2006
DOI: 10.1590/s0034-89102006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for HIV testing during pregnancy in Southern Brazil

Abstract: OBJECTIVE:To assess HIV testing rate and determine risk factors for not have been tested during pregnancy. METHODS:A cross-sectional study was carried out in Porto Alegre, Southern Brazil, from December 2000 to February 2001. Socioeconomic, maternal and healthcare variables were obtained by means of a standardized questionnaire. Crude and adjusted odds ratios and their 95% confidence intervals were obtained in logistic regression models. RESULTS:A total of 1,642 mothers were interviewed. Of them, 94.3% reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(18 reference statements)
3
6
0
1
Order By: Relevance
“…This is consistent with a study conducted in Vietnam and other countries which indicated that pregnant women who worry about their husband reaction in case he learnt that they were tested positive were refusing HIV testing during their ANC visit [18-20]. Moreover, our study finding is consistent with a study conducted in Uganda, Tanzania, Zambia and Vietnam.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a study conducted in Vietnam and other countries which indicated that pregnant women who worry about their husband reaction in case he learnt that they were tested positive were refusing HIV testing during their ANC visit [18-20]. Moreover, our study finding is consistent with a study conducted in Uganda, Tanzania, Zambia and Vietnam.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also showed that pregnant women who attended secondary education or above were more likely to be tested for HIV compared with pregnant women who did not attend formal education, consistent with previous studies in Nigeria and Tanzania that showed an association between higher educational level and HIV testing [7, 9]. However other studies level of education was a statistically significant factor for HIV testing [25, 26].…”
Section: Discussionsupporting
confidence: 91%
“…Similar rates of acceptance were also found in other studies conducted in Brazil, including when HIV testing was offered during labor. 6,9,12 The wide availability of free HIV prevention and care services in Brazil, which includes highly potent antiretroviral therapy and HIV testing, as well as the policy of universal offering of HIV testing to pregnant women would be among the several factors contributing to the high rate of HIV testing acceptance seen in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…A large study conducted in Porto Alegre for one year during the same period covered by the present study also found a high proportion of unawareness of being tested/compulsory HIV testing. 9 The literature review we carried out did not fi nd any study in the other three cities adressing the issue of compulsory HIV testing. In a study performed in Spain to compare self-reporting with medical record information regarding HIV testing, unawareness of having been tested was found in 10.7% of the study population.…”
Section: Discussionmentioning
confidence: 99%